A Rare Thyroid Gland Emergency: Thyroid Abscess - Artas, Hakan; Eroglu, Yesim (Emergency Medicine Physicians Assoc Turkey, 2021)
Introduction: Thyroid abscess is a serious head and neck infection that may easily be overlooked. It is a rare disease with serious complications when the diagnosis is delayed. In this paper, we present a case of thyroid abscess who presented with fever, fatigue, neck pain and swelling, and rapidly deteriorated general condition. Case Report: A 28-year-old female patient had painful swelling and redness on the left side of the neck. She had fever, fatigue, and dysphagia. Laboratory tests revealed leukocytosis, elevated CRP, and sedimentation rate. The patient who was detected to have thyroid abscess on ultra-sonography and computed tomography was discharged with recovery through surgery and appropriate antibio-therapy. Conclusion: Thyroid gland abscess is a rare, serious clinical condition with high morbidity and mortality. Thyroid abscess should be kept in mind while performing radiological evaluation in cases presenting with swelling and redness in the neck. In these cases, quite good clinical outcomes may be achieved with early diagnosis and appropriate treatment.
Keywords: Thyroid; abscess; emergency